A native sulfur deposit in Gale crater, Mars - Scott J. VanBommel; Jeff A. Berger; Penelope L. King; William E. Dietrich; Ralf Gellert; Lucy M. Thompson; Ashwin R. Vasavada; Alexander B. Bryk; Edwin S. Kite; Joanna V. Clark; Aster C. Cowart; Rebecca M. E. Williams; et al. (Science, 2026)
Martian rocks are known to contain sulfur-bearing species, including sulfates and sulfides. These compounds record a sulfur cycle that operated over Mars’ geological evolution. We used the Curiosity rover to investigate a deposit of light-toned stones in Gediz Vallis, within Gale crater on Mars. We find that the stones are composed of native sulfur. The sulfur deposit appears to have formed in place, within a sinuous entrenched canyon cut into the floor of Gediz Vallis. The presence of native sulfur implies that a sulfur enrichment pathway involving buoyant subsurface fluids operated on ancient Mars. We propose that the primary source of this sulfur was magmatic vapor, which cooled in the near subsurface cryosphere and was released by decompression during the erosion of Gediz Vallis.